2018
DOI: 10.1074/jbc.ra118.004345
|View full text |Cite
|
Sign up to set email alerts
|

The actin filament bundling protein α-actinin-4 actually suppresses actin stress fibers by permitting actin turnover

Abstract: Cells organize actin filaments into contractile bundles known as stress fibers that resist mechanical stress, increase cell adhesion, remodel the extracellular matrix, and maintain tissue integrity. α-actinin is an actin filament bundling protein that is thought to be essential for stress fiber formation and stability. However, previous studies have also suggested that α-actinin might disrupt fibers, making the true function of this biomolecule unclear. Here we use fluorescence imaging to show that kidney epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 76 publications
(86 reference statements)
3
24
1
Order By: Relevance
“…For instance α-actinin competes with tropomyosins, which protects actin filaments from cofilin induced severing and activate myosinII (Gateva et al, 2017). This competition determines the rate of actin turn-over and thereby the assembly of stress fiber formation and the regulation of cell motility (Kemp and Brieher, 2018). We also found that alpha-actinin knockdown perturbs the orientation of contractile forces.…”
Section: Discussionmentioning
confidence: 59%
“…For instance α-actinin competes with tropomyosins, which protects actin filaments from cofilin induced severing and activate myosinII (Gateva et al, 2017). This competition determines the rate of actin turn-over and thereby the assembly of stress fiber formation and the regulation of cell motility (Kemp and Brieher, 2018). We also found that alpha-actinin knockdown perturbs the orientation of contractile forces.…”
Section: Discussionmentioning
confidence: 59%
“…The underlying mechanism appears to be based on the ability of ACTN4 to bundle actin filaments (Honda et al, 1998;Winkelman et al, 2016), however, we also observed a role for actin assembly by nuclear ACTN4. Interestingly, ACTN4 has been previously shown to affect actin assembly or filament turnover (Kemp and Brieher, 2018). Hence, it is conceivable that a coordinated mechanism between actin assembly and bundling might be at work, further emphasizing the highly complex and dynamic nature of the actin cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…ACTN4 is a conserved, abundant, and ubiquitous actin-binding protein belonging to the spectrin superfamily, which modulates a wide range of processes [51][52][53][54][55][56][57][58]. As a component of the cytoskeleton, ACTN4 plays crucial roles in remodeling of the actin cytoskeleton, and in stress fiber formation and stability [59,60]. Stress fibers are contractile bundles of actin filaments that span the entire length of the cell and are anchored at both ends at focal adhesions, so actin presents a challenging hurdle to virus entry [61,62].…”
Section: Discussionmentioning
confidence: 99%